2019
DOI: 10.3390/su11051320
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Change and Driving Factors: Contribution Analysis in the Loess Plateau of China during 2000–2015

Abstract: Judging vegetation change and analyzing the impacts of driving factors on vegetation change are important bases on which to evaluate the effects of ecological engineering constructions on the Loess Plateau and to support ecological construction planning decisions. The authors applied time-section difference analysis and trend analysis methods to analyze the temporal–spatial characteristics of vegetation change on the Loess Plateau from 2000 to 2015. Then, complex linear regression analysis and residual analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In this research, the soil and water retention that resulted from revegetation and terrace construction was larger than the retention that resulted from the construction of check dams, which agrees with previous research by Wang et al [10]. However, high water consumption by new vegetation has aroused extensive concerns [31], since many studies have shown decreased water availability after large-scale vegetation rehabilitation that aggravated existing water scarcity, and that led to soil desiccation in the water-scarce Loess Plateau [22,32].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this research, the soil and water retention that resulted from revegetation and terrace construction was larger than the retention that resulted from the construction of check dams, which agrees with previous research by Wang et al [10]. However, high water consumption by new vegetation has aroused extensive concerns [31], since many studies have shown decreased water availability after large-scale vegetation rehabilitation that aggravated existing water scarcity, and that led to soil desiccation in the water-scarce Loess Plateau [22,32].…”
Section: Discussionsupporting
confidence: 89%
“…Some researchers claimed that decreases in runoff or sediment over time might be caused by decreasing rainfall [31], and records from 20 meteorological stations in the Yellow River basin showed that the rainfall has decreased significantly from 1951 to 2000 [67,68]. However, in our study area, both watersheds had the same rainfall erosivity, so the erosion prevention and water retention would have resulted from the restoration practices rather than from any change in rainfall.…”
Section: Discussionmentioning
confidence: 57%
“…The drought conditions during the study period (2006–2007) only changed the residual rate and did not cause a change in direction. This also indicates that the influence of climatic factors on residuals is smaller than that of human factors [ 49 , 50 ], thus highlighting that the correct identification of climate change and vegetation changes caused by human activities is critical to the implementation of appropriate land-use policies and grassland management.…”
Section: Discussionmentioning
confidence: 99%
“…There are three grassland types, namely, alpine meadow, alpine grassland, and alpine desert from southeast to northwest [24]. For LP, the altitude is 300-3000 m, the MAT is 3.7-14.0˚C, and the MAP is~110-860 mm, and this plateau belongs to the dry with cold semi-arid climate (Bsk) and snow with dry winter climate (Dwa) [25][26][27]. The vegetation types were distributed from the southeast to northwest with warm forest, warm forest grassland, warm typical grassland, and warm desert grassland [28].…”
Section: Plos Onementioning
confidence: 99%